Conference Report on Música Analítica 2023. Interdisciplinary Approaches to Musical Time - Martins, José (Revue musicale OICRM)

(untitled) (Observatoire interdisciplinaire de création et recherche en musique (OICRM), 2025)
Música Analítica 2023, held at the University of Coimbra, brought together an international and interdisciplinary community to examine musical time as a multifaceted analytical, perceptual, and cultural phenomenon. Across keynotes, plenaries, and twelve thematic sessions, scholars from music theory, cognitive science, ethnomusicology, performance, philosophy, and related fields explored how time is structured, experienced, and conceptualized in diverse musical practices. Discussions ranged from microtiming, polyrhythm, and temporal cognition to historical, cross-cultural, and technological perspectives. Serving as a conceptual precursor to the ERA Chair project MusicAnalytica, the conference articulated a forward-looking framework for musical time as a transdisciplinary research nexus.